Production of Gluconic Acid from MolassUsing Aspergillusniger Fungi and Optimization of Production Conditions (Damascus University Journal of agriculture sciences, 2022)
During the past fifty years, gluconic acid and its derivatives have gained increasing interest in the food, pharmaceutical, textile, and construction industries, so this research aimed to produce gluconic acid by fermenting molasses using Aspergillus niger and optimization of production conditions, 10 isolates have the ability to produce acid after testing 20 isolates of Aspergillus niger taken from the National Commission for Bio technology. Results showed that the most productive isolate was (An6), with122.3 g / lgluconic acid. Then this isolate was used in the optimization of production conditions (aeration speed - temperature - pH - sugar concentration - incubation time) using the Minitab statistical analysis program. The optimal parameters were: aeration speed of 150 rpm- pH: 6 temperature:°C 30 - sugar concentration: 234g / l sugar- incubation time: 6 days
Keywords: Gluconic Acid; Aspergillus niger; Molasses; Surface liquid fermentation.fermentation